Intelligent intrusion prevention system for households based on system-on-chip computer - Rashid, Md Tahmid; Abir, Imtiaz Kalam; Shourove, Niaz Sharif; Muntaha, Rakibun; Rhaman, Md Khalilur (© 2016 IEEE, 2018)
This conference paper was published in the IEEE Xplore [ © 2016 IEEE] and the definite version is available at : http://doi.org/10.1109/CCECE.2016.7726816 The Journal's website is at: http://ieeexplore.ieee.org/document/7726816/